Analisis Permasalahan Turunnya Minat Belajar Peserta Didik di SMPS Al-Washliyah 27 Amplas - Nurussakinah Daulay; Nabiilah Husnaa Br. Tarigan; Amanda Junita Tanjung; Asbih Fahrezi Tanjung; Halimah Halimah; Rohimatun Fadilah Munte (SAP (Susunan Artikel Pendidikan), 2023)
The problem of decreasing interest in learning students in Medan is a problem that often occurs at various levels of education; therefore, efforts must be made to find out the cause of the problem. Thus, this study aims to reveal the problem of decreasing interest in learning students at SMPS Al-Washliyah 27 Amplas. This research method uses a descriptive qualitative approach with a case study approach. Data collections of this study are observation, interview, and documentation study techniques with Miles and Huberman analysis, namely data reduction, data presentation, and conclusions. The research was conducted on 17 October–20 October 2022. The subjects of the study were students and teachers at SMPS Al-Washliyah 27 Amplas. The results revealed that the problem of decreasing interest in learning students at SMPS Al-Washliyah 27 Amplas became a high category of problems caused by 2 factors, namely internal and external which caused students and educators to have difficulty overcoming them. However, educators still try to overcome the problem of decreasing demand for learning by implementing good learning strategies. However, the efforts that have been made lack of support from students, the environment, and other related parties have caused difficulties in overcoming the problem of decreasing interest in learning students.